2020
DOI: 10.3390/su12156018
|View full text |Cite
|
Sign up to set email alerts
|

Urease and Nitrification Inhibitors—As Mitigation Tools for Greenhouse Gas Emissions in Sustainable Dairy Systems: A Review

Abstract: Currently, nitrogen fertilizers are utilized to meet 48% of the total global food demand. The demand for nitrogen fertilizers is expected to grow as global populations continue to rise. The use of nitrogen fertilizers is associated with many negative environmental impacts and is a key source of greenhouse and harmful gas emissions. In recent years, urease and nitrification inhibitors have emerged as mitigation tools that are presently utilized in agriculture to prevent nitrogen losses and reduce greenhouse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 94 publications
1
57
0
1
Order By: Relevance
“…Their use showed many benefits for what concerns inhibitors, although little is known about their potential to enter the food chain (Byrne et al, 2020), even if this phenomenon has been already…”
Section: Impact Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Their use showed many benefits for what concerns inhibitors, although little is known about their potential to enter the food chain (Byrne et al, 2020), even if this phenomenon has been already…”
Section: Impact Assessmentmentioning
confidence: 99%
“…The authors also reported that both in planta toxicity assays and V. fischeri bioluminescence inhibition test only showed detrimental effects at very high doses, which are nearly impossible to be found in agricultural conditions. Also, for NBPT urease inhibitor, a plant uptake in maize, pea, and spinach has been observed (Cruchaga et al, 2011;Zanin et al, 2015), with potential inhibition of leaf and root urease activity (Byrne et al, 2020). In this context, the challenge is to find eco-friendly, non-toxic, and low toxicity for plants and chemically stable inhibitors, efficient at low concentrations, compatible with urea fertilizers, and having sustainable costs.…”
Section: Impact Assessmentmentioning
confidence: 99%
“…This indicates that ammonium-based compound fertilisers could potentially be a similar mitigation measure to the use of urea + NBPT to reduce N 2 O emissions from temperate grassland. The addition of inhibitors incurs extra costs and there are issues around acceptability from farmers and milk processors due to perceptions around residues [20,33]. However, a recent study investigating the potential for residues observed no residue issues associated with the use of NBPT with urea [34].…”
Section: The Effect Of Fertiliser Formulations On N 2 O Emissionsmentioning
confidence: 99%
“…In Ireland, the use of urea with NBPT is encouraged as a mitigation measure to reduce both ammonia and nitrous oxide emissions [ 2 ]. In 2005, it was reported that 54% of non-CO 2 greenhouse gas emissions were produced by agriculture [ 3 , 4 ]. Studies have also shown that NBPT enables efficient utilisation of urea by delaying urea hydrolysis, making N available to crops/plants, thereby enhancing agricultural yield and profitability but reducing ammonia losses.…”
Section: Introductionmentioning
confidence: 99%